Implementasi Model Quantum Teaching Dalam Meningkatkan Pemahaman Belajar Siswa pada Mata Pelajaran Al-Quran Hadis Kelas VII MTs Swasta Teladan Gebang - Maulida Maulida (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
The purpose of this study: To determine the application of the Quantum Teaching model in learning activities in the field of study of Al-Qur'an Hadith in MTs. Personal Exemplary Gebang. To determine the ability of students' understanding of learning the field of study of the Qur'an and Hadith in MTs. Personal Exemplary Gebang. To find out the application of the Quantum Teaching model in an effort to improve students' understanding of learning the field of study of the Qur'an and Hadith in MTs. Personal Exemplary Gebang. This research is a descriptive qualitative research, namely the data collected in the form of words and descriptions. According to Lexy J Moleong that "qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior". While descriptive research is a form of research that aims to describe or describe existing phenomena, both natural phenomena and phenomena engineered by humans. The results of the study show that: (1) The application of the Quantum Teaching model to Al-Qur'an Hadith subjects has been maximally applied in relation to the implementation of learning during the COVID-19 pandemic which requires online teaching and learning activities. So that learning using Quantum Teaching is very appropriate to be applied in MTs. Private Exemplary Gebang; (2) The ability to understand student learning in the field of study of the Qur'an and Hadith in class VII MTs. The Gebang Private Example has been implemented optimally with the efforts of teachers in the field of study in improving students' understanding abilities in learning; (3) The application of the Quantum Teaching model in improving the ability to understand the learning of the Qur'an and Hadith in class VII MTs students. The Gebang Private Example has been implemented well and there has been an increase since the beginning of the pre-meeting, namely the number of students who got a complete score, namely 29.7% of students who got a complete score in the Qur'an Hadith field of study, at the first meeting it increased to 46% of students who completed activity. study the Qur'an Hadith on the material to understand the short surah of the Qur'an. At the second meeting the level of completeness of students in learning Al-Qur'an Hadith was 78.3% for class VII MTs. Personal Exemplary Gebang. Then analyzed from Meeting III, student completeness reached 100%.. Private Exemplary Gebang can be increased through the application of the Quantum Teaching model.